2013
DOI: 10.1371/journal.pntd.0002156
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Exposure to Rift Valley Fever Virus Causes Earlier and More Severe Neuropathology in the Murine Model, which Has Important Implications for Therapeutic Development

Abstract: Rift Valley fever virus (RVFV) is an important mosquito-borne veterinary and human pathogen that can cause severe disease including acute-onset hepatitis, delayed-onset encephalitis, retinitis and blindness, or a hemorrhagic syndrome. Currently, no licensed vaccine or therapeutics exist to treat this potentially deadly disease. Detailed studies describing the pathogenesis of RVFV following aerosol exposure have not been completed and candidate therapeutics have not been evaluated following an aerosol exposure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
81
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 26 publications
(30 reference statements)
5
81
1
Order By: Relevance
“…RVFV is another member of the Phlebovirus genus, for which both the in vitro and in vivo effects of ribavirin have been reported (22)(23)(24). Ribavirin reduced RVFV proliferation in a dose-dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…RVFV is another member of the Phlebovirus genus, for which both the in vitro and in vivo effects of ribavirin have been reported (22)(23)(24). Ribavirin reduced RVFV proliferation in a dose-dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Peters et al reported that ribavirin at 23 mg/ml showed 2-log inhibition against RVFV in Vero cells (23). In animal models, ribavirin treatment (75-100 mg/kg/day) led to a 60z-75z survival rate in RVFV-inoculated mice (22)(23)(24), while it suppressed viremia in RVFV-infected monkeys (30 mg/kg/day, more than 2-log reduction of viral titers) (23). In the present study, the EC 99 of ribavirin in Vero cells against SFTSV .…”
mentioning
confidence: 99%
“…However, most clinical cases occur after contact with blood, aborted fetuses, and placenta of viremic animals. Farmers, veterinarians, slaughterhouse workers, and butchers are thus the most exposed to the risk of RVF, as well as any people attending the slaughtering of viremic animals (11): Blood aerosol produced on this occasion is highly infectious (12). The virus is not transmitted from person to person.…”
mentioning
confidence: 99%
“…23,24 However, in animal models, ribavirin has caused anemia and teratogenic effects, which has limited the application to compassionate use under investigational new drug protocols. 5,6 There are also other potential drugs in the development stage. 24,25 Therefore, there is a great need to find new drugs to treat human infection with better efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…5 The efficacy in humans remains to be proven and there are undesirable side effects. 6 RVFV is an enveloped, negatively stranded RNA virus composed of three RNA segments, complexed with the nucleocapsid (N) protein.…”
Section: Introductionmentioning
confidence: 99%